Drying kinetics of pickled jalapeño pepper (Capsicum annuum L.): Secado de una variedad de Capsicum - Guerrero Alva, Dániza Mirtha; Motta Guerrero, Renato (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Pickled jalapeño pepper (Capsicum annuum L.) was dried in hot air at 70°C, 50°C, and 35°C, and in a no-frost refrigeration chamber (10°C); finding the drying kinetic curves, the drying time (19 h to 744 h), high relationship between moisture rate and drying time and between temperature and drying time; effective diffusivity (6.59E-11 m2.s-1 and 1.2176E-9 m2.s-1), activation energy (39.90 kJ/mol), soluble solids, pH, and vitamin C retention of 133% at 10°C but losing at least 50% of vitamin C by drying with hot air.